Some aspects of the forced resettlement of selected peoples of the Soviet Union and its consequences - Kowalska, Ewa (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the problem of the forced resettlement of peoples living within the Soviet Union and its political, social, and cultural consequences. The author aims to explain the ideological foundations of Soviet nationality policy and the mechanisms that led to the mass deportation of entire ethnic groups. The study is based on the analysis of party documents, archival materials, and publications concerning Soviet nationality policy. The author notes that the Soviet state inherited from the Russian Empire an extremely diverse ethnic structure, the maintenance of which required reconciling the proclaimed right of nations to self-determination with the desire to preserve state integrity. Particular attention is devoted to Joseph Stalin’s views on the classification of nations and methods of integrating them into the Soviet system. The analysis demonstrates that nationality issues became both the basis of administrative divisions and an instrument of political control. The author discusses the ideological and practical justifications for the deportation of entire communities, which were explained in terms of economic needs, state security, and the colonization of sparsely populated areas of the USSR. The conclusions indicate that forced resettlements constituted an important component of the Soviet system of governing a multinational state, leading to lasting demographic, social, and cultural transformations.